Diversity of esterase and lipase producing haloalkaliphilic bacteria from Lake Magadi in Kenya. (16th October 2019) - Kiplimo, Denis; Mugweru, Julius; Kituyi, Sarah; Kipnyargis, Alex; Mwirichia, Romano
Abstract: Lipids are hydrocarbons comprised of long‐chain fatty acids and are found in all living things. In the environment, microorganisms degrade them to obtain energy using esterases and lipases. These enzymes are nowadays used in different industrial applications. We report isolation of 24 bacteria with esteresic and lipolytic activity from Lake Magadi, Kenya. The isolates were characterised using morphological, biochemical, and molecular methods. Isolates grew at an optimum salt concentration of 5–8% (w/v), pH range of 8.0–9.0, and temperature range of 35–40°C. The isolates were positive for esterase and lipase assay as well as other extracellular enzymes. Phylogenetic analysis of the 16S ribosomal RNA gene showed that the isolates were affiliated to the genus Bacillus, Alkalibacterium, Staphylococcus, Micrococcus, Halomonas, and Alkalilimnicola . None of the bacterial isolates produced antimicrobial agents, and all of them were resistant to trimethoprim and nalidixic acid but susceptible to streptomycin, amoxillin, chloramphenicol, and cefotaxime. Growth at elevated pH, salt, and temperature is an indicator that the enzymes from these organisms could function well under haloalkaline conditions. Therefore, Lake Magadi could be a good source of isolates with the potential to produce unique biocatalysts for the biotechnology industry.